Learning sustainability by developing a solar dryer for microalgae retrieval - Benedita Malheiro; Cristina Castro Ribeiro; Manuel Fernando Silva; Nídia Sá Caetano; Paulo Ferreira; Pedro Guedes (OmniaScience, 2016)
Excessive fossil fuel consumption is driving the search for alternative energy production solutions and, in particular, for sustainable sources of energy such as microalgae, from which biodiesel, among other useful compounds, can be obtained. After producing the microalgae, they must be harvested and dried. Existing drying solutions consume too much energy and are, therefore, expensive and unsustainable. The goal of this EPS@ISEP Spring 2013 project was to develop a solar microalgae dryer for the microalgae laboratory of ISEP. A multinational team of five students from distinct fields of study was responsible for designing and building the solar microalgae dryer prototype. The prototype includes a control system to ensure that the microalgae are not destroyed during the drying process. The solar microalgae dryer works as a distiller, extracting the excess water from the microalgae suspension. This paper details the design steps, the building technologies, the ethical and sustainable concerns and compares the prototype with existing solutions. The proposed sustainable microalgae drying process is competitive as far as energy usage is concerned. Finally, the project contributed to increase the team's sustainable development awareness, active learning and motivation.